2008
DOI: 10.1088/0953-8984/20/33/335204
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in disordered organic host–guest systems: effects of carrier density and electric field

Abstract: We investigate charge transport in disordered organic host-guest systems with a bimodal Gaussian density of states (DOS). The energy difference between the two Gaussians defines the trap depth. By solving the Pauli master equation for the hopping of charge carriers on a regular lattice with site energies randomly drawn from the DOS, we obtain the dependence of the charge-carrier mobility on the relative guest concentration, the trap depth, the energetic disorder, the charge-carrier density and the electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…The approach is based on the results of transport modeling using a master-equation ͑ME͒ approach. In an earlier study, 27 it was already found that the effect of FID on the mobility as obtained from ME modeling is significantly different from the effect as predicted by a semianalytical effective-medium theory. Using the ME modeling results, we show that the HL model can be extended to finite values of the electric field by using a generalized FD distribution function that depends only on the shape of the host DOS and the electric field, and not on the guest DOS.…”
Section: Introductionmentioning
confidence: 72%
“…The approach is based on the results of transport modeling using a master-equation ͑ME͒ approach. In an earlier study, 27 it was already found that the effect of FID on the mobility as obtained from ME modeling is significantly different from the effect as predicted by a semianalytical effective-medium theory. Using the ME modeling results, we show that the HL model can be extended to finite values of the electric field by using a generalized FD distribution function that depends only on the shape of the host DOS and the electric field, and not on the guest DOS.…”
Section: Introductionmentioning
confidence: 72%
“…From an estimate of the effect based on an analysis given in Ref. 27 for the case of a bimodal Gaussian DOS, we have found that the effect is very small for the systems and experimental conditions considered in this Brief Report. In our analysis, FID was therefore neglected.…”
mentioning
confidence: 81%
“…It was used successfully for treating the mobility in a bimodal Gaussian DOS, 26 as confirmed by numerically exact masterequation calculations. 27 It is known that in the presence of a field the effective mobility in a system containing trap states can be larger than as obtained from the MTR model. 28 For materials with the shape of the DOS assumed in this Brief Report ͑Fig.…”
mentioning
confidence: 96%
“…In this regime, a more complicated model is required. 26 We remark that for higher concentrations the quality of the fit was less sensitive to the value of N t , leading to a large error margin in N t .…”
mentioning
confidence: 83%